1987
DOI: 10.1210/jcem-65-1-17
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the Suppressor-Inducer T Cell Subset and Increase in the Helper T Cell Subset in Thyroid Tissue from Patients with Graves' Disease

Abstract: The expression of surface markers associated with activation and characterization was compared among T cells in thyroid glands and peripheral blood of 10 patients with Graves' hyperthyroidism receiving chronic antithyroid drug therapy, in peripheral blood of 15 patients with untreated hyperthyroid Graves' disease, and in peripheral blood of 21 normal subjects using two-color flow cytometry. In the chronically treated Graves' disease patients, the percentage of activated T cells (HLA-DR+ T cells) among total T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
24
0
2

Year Published

1988
1988
2000
2000

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 22 publications
4
24
0
2
Order By: Relevance
“…The accumulation of activated CD4 ϩ T cells in thyroid gland from patients with Graves' disease has been demonstrated (Ishikawa et al, 1987;Ishikawa et al, 1993), and restricted T cell receptor gene usage was recently demonstrated in thyroidal infiltrate from Graves' patients (Davies et al, 1991a;1991b). These data suggest that Ag-specific T cell activation is present in thyroid glands from Graves' patients.…”
Section: Kawakami Et Almentioning
confidence: 76%
See 1 more Smart Citation
“…The accumulation of activated CD4 ϩ T cells in thyroid gland from patients with Graves' disease has been demonstrated (Ishikawa et al, 1987;Ishikawa et al, 1993), and restricted T cell receptor gene usage was recently demonstrated in thyroidal infiltrate from Graves' patients (Davies et al, 1991a;1991b). These data suggest that Ag-specific T cell activation is present in thyroid glands from Graves' patients.…”
Section: Kawakami Et Almentioning
confidence: 76%
“…In vitro studies have also shown that thyrocytes function as stimulatory APCs to T cells (Eguchi et al, 1995;Eguchi et al, 1988;Matsuoka et al, 1996;Nagataki and Eguchi, 1992), suggesting the presence of antigen (Ag)-dependent active cellular interactions between thyrocytes and T cells in thyroid glands of patients with Graves' disease. Activated CD4 ϩ T cells have been found in thyroid glands of patients with Graves' disease (Eguchi, et al, 1995;Eguchi et al, 1988;Ishikawa et al, 1987;Ishikawa et al, 1993;Nagataki and Eguchi, 1992). Results of in vitro studies have shown that activated CD4 ϩ T cell clone express Fas ligand (FasL) and kill Fas ϩ target cells (Ju et al, 1994;Rouvier et al, 1993;Stalder et al, 1994).…”
mentioning
confidence: 99%
“…In contrast, the percentage of circulating CD8+ cells was lower and that of HLA-DR+ cells was higher in patients with Graves' disease than those in normal controls [12][13][14]. Since then, the percentage of activated T cell subsets in patients with autoimmune thyroid diseases has been reported, using two-color dye labeling and dual laser activated cell sorter analysis [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The activated T cells in various types of autoimmune diseases, KUSHIMA et al including Graves' disease, have been measured with monoclonal antibodies to the surface antigens of T cells [141. A few years later, the percentage of peripheral blood activated T cell subsets in patients with autoimmune thyroid diseases, measured by two-color dye labelling and dual laser flow cytometry, were reported [15][16][17][18]. In the majority of the former reports on thyroid diseases such as Graves' disease and Hashimoto's thyroiditis, the percentages of all activated matured T (HLA-DR+CD3+), activated helper/inducer T (HLA-DR+CD4+), and activated suppressor/cytotoxic T (HLA-DR+CD8+) cells in the peripheral blood were higher than those of healthy volunteers, but the results were conflicting because of differences in methods and subjects.…”
mentioning
confidence: 99%
“…These T cells are mainly CD4+ memory cells [9][10][11] . On the other hand, thyroid follicular cells in GD patients aberrantly express HLA class II molecules and present antigens [12].…”
mentioning
confidence: 99%